2009
DOI: 10.2147/ndt.s5880
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and behavioral disease during developmental age: the importance of the alliance with parents

Abstract: The aim of the study is to analyze the clinician’s alliance with parents during the diagnostic process in relation to therapeutic compliance and clinical evolution of individuals aged 0–11 years. The sample was formed by 84 individuals aged 0 to 11 years (18 < 6 years, 66 aged 6 to 11 years; 62 males and 22 females) who came to the Neuropsychiatric Unit for Children and Adolescents for a consultation regarding psychorelational and behavioral problems. Neuropsychiatric consultation took place in five diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
0
14
1
Order By: Relevance
“…It is not only the influence of each parent separately that would provide a matrix for the daughter’s emotional development but also, and even more significantly, the affective regulation of the parental couple, as expressed in the complex relational dynamics of the triad (Kooiman et al, 2004; Gatta et al, 2016a). Evaluating the couple relationship, starting from the conflicts and distress, can therefore prove to be useful in order to better understand the functioning of the whole family and therefore plan treatments, tailored for the patient as well as for the family needs (Gatta et al, 2009, 2011; Mannarini et al, 2016a). A relationship in which emotions and thoughts are shared within the attachment relationship (Mannarini and Boffo, 2014) with the father as well as with the mother is able to facilitate the development of an adaptive affective regulation and a rich inner emotional life in the offspring (Taylor et al, 1997), thus enhancing the possibility of recovery of the daughter with anorexia nervosa.…”
Section: Discussionmentioning
confidence: 99%
“…It is not only the influence of each parent separately that would provide a matrix for the daughter’s emotional development but also, and even more significantly, the affective regulation of the parental couple, as expressed in the complex relational dynamics of the triad (Kooiman et al, 2004; Gatta et al, 2016a). Evaluating the couple relationship, starting from the conflicts and distress, can therefore prove to be useful in order to better understand the functioning of the whole family and therefore plan treatments, tailored for the patient as well as for the family needs (Gatta et al, 2009, 2011; Mannarini et al, 2016a). A relationship in which emotions and thoughts are shared within the attachment relationship (Mannarini and Boffo, 2014) with the father as well as with the mother is able to facilitate the development of an adaptive affective regulation and a rich inner emotional life in the offspring (Taylor et al, 1997), thus enhancing the possibility of recovery of the daughter with anorexia nervosa.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a previous study suggested that working with their parents benefits the young patients, responding both to the parent's need to report their children's difficulties and to the discomfort expressed by the children (Gatta et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Among those with whom an adequate alliance was constructed we found a slight prevalence of adolescents who were the offspring of intact parental couples (56.9% intact couples vs 43.8% single-parent families), whole among those with whose parents it was impossible to construct an effective working alliance, we found a marked prevalence of adolescents coming from single-parent families (31.3% singleparent families, 3.9% intact parental couples). This finding can be placed in relation to the lack of a sufficiently supportive family environment, as documented by previous studies, and to the fact that single-parent families have to be seen as a possible factor of risk both for the onset of psychopathologies and for the failure of their treatment (Gatta et al, 2009a(Gatta et al, , 2009bHanington et al, 2011;Manzano et al, 1993).…”
Section: Mode Of Participationmentioning
confidence: 76%
“…This therapeutic method is applicable to various mental disorders, both in developmental age and in adults, and its efficacy has been acknowledged internationally (Bartels et al, 2004;Bond et al, 2001). Within this network, it is also worth emphasizing the importance of the cooperation with the adolescents' families and the proper exploitation of a personal relationship with them so that they can share the experiences of suffering caused by their child's disorder, also with a view to reinforcing the working alliance with them (Gatta et al, 2009b(Gatta et al, , 2010b(Gatta et al, , 2010cHawley & Weisz, 2005;Marcelli, 2009;Woolfenden et al, 2009). …”
mentioning
confidence: 99%
See 1 more Smart Citation